2016
DOI: 10.5539/ijef.v8n9p34
|View full text |Cite
|
Sign up to set email alerts
|

Relating Company Size and Financial Performance in Agricultural Firms Listed in the Nairobi Securities Exchange in Kenya

Abstract: Company/firm size is among the many variables that is significant in assessing the profitability of a company. Therefore, this paper seeks to evaluate the effect of company size on the financial performance of listed agricultural companies in Kenya. The theory of economies of scale that links benefits arising from company size, cost management and production volumes was utilized. Secondary data was extracted from the annual reports comprising of financial statement from the period 2003 to 2013 and analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 17 publications
2
29
0
5
Order By: Relevance
“…While Maggina and Tsaklanganos (2012) found that company growth as measured by asset growth also affected the company's performance. Odalo et al (2016)…”
Section: Hypothesis Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While Maggina and Tsaklanganos (2012) found that company growth as measured by asset growth also affected the company's performance. Odalo et al (2016)…”
Section: Hypothesis Test Resultsmentioning
confidence: 99%
“…With high sales growth, it is expected that it will be able to increase the company's profits which will ultimately improve the company's performance. The results of Dada and Ghazal (2016), Maggina and Tsaklanganos (2012), Juwita (2018) and Odalo et al (2016) found a positive influence between the growth of companies and corporate performance.…”
Section: Sales Growth and Corporate Performancementioning
confidence: 95%
See 1 more Smart Citation
“…Banafa, (2016)anticipated that liquidity & firm's size affects positively on the financial performance of non-financial organizations indexed at Nairobi securities exchange during 2009-2013. Odalo & Achoki, (2016)suggested that liquidity in the terms of liquidity-ratio influence positively & significantly on the financial performance(ROA and ROE) of agro-companies in Kenya. But liquidity ratio affects positively and insignificantly on the financial performance variable earnings per share.…”
Section: 2mentioning
confidence: 98%
“…It reflects the managements' effectiveness and efficiency in utilization of resources of a firm (Miles & Van Clieaf, 2017). Thus, firms are mostly concerned with their financial performance to ensure their long term survival (Odalo, Achoki, & Njuguna, 2016). Moreover, strong FP of a firm gives a greater ability to undertake higher financial risk in capital budgeting (Gómez-Bezares, Przychodzen, & Przychodzen, 2017).…”
Section: Introductionmentioning
confidence: 99%